Exploring the effect of CNTs and pluronic on characteristics and stability of polyethersulfone (PES) and polyvinylidene fluoride (PVDF) membranes - Nasrul Arahman; Cut Meurah Rosnelly; Muhammad Prayogie Aulia; Rinal Dia'ul Haikal; Yusni; Aulia Chintia Ambarita; Poernomo Gunawan; Ismail Koyuncu; Hideto Matsuyama; Noriaki Kato; Ryosuke Takagi (Case Studies in Chemical and Environmental Engineering)
The accumulation of organic matter and colloidal particles on the membrane surface during the filtration process requires periodic chemical cleaning, potentially impacting the membrane properties and characteristics. Unfortunately, in recent years research into membrane stability against cleaning agents has often been neglected. This should be a crucial part to be prepared as membrane use in the industrial world, therefore this research aims to study the aging of polyethersulfone (PES) and polyvinylidene fluoride (PVDF) membranes modified with single-walled carbon nanotubes (CNTs) and Pluronic (PF). Membranes were prepared using phase inversion method and then treated by soaking in a 5 % sodium hypochlorite (NaClO) solution for 1 hour. Changes in the properties and performance of each membrane were investigated before and after treatment. Overall, the results show that the modified CNTs/PF-PES has better stability in various aspects of analysis such as functional groups, chemical composition, morphology, and hydrophilicity. The CNTs/PF-PES water contact angle increases from 59.4° to 64.7° while CNTs/PF-PVDF water contact angle increases until 69.1°. In addition, CNTs/PF-PES performance also shows more stable results with a flux decrease of 1.31 L/m2.h only, while CNTs/PF-PVDF experiences a decrease of up to 16.31 L/m2.h. Therefore, it can be concluded that CNTs and PF modification is better and more stable on PES membrane matrix compared to PVDF.